Concerns about and stimuli of COVID-19 vaccination hesitancy among diverse occupational groups in metropolitan areas of China: a cross-sectional study - Jie Gu; Zhaoxin Wang; Qian Huang; Jiaoling Huang; Haiying Chen; Zhilan Xie; Yinliang Tan; Yuge Yan; Xiaoqing Gu (BMJ Open)
Objectives In this study, we aimed to identify concerns and stimuli regarding COVID-19 vaccination acceptance and to compare the findings by occupation.Methods We conducted a cross-sectional study of individuals vaccinated against COVID-19 between 1 April and 30 June 2021 in four metropolitan areas of China. A total of 20 863 participants completed questionnaires, 20 767 of which were eligible for analysis. We used ordered logistic regression to assess the association of vaccination concerns and stimuli with vaccination hesitancy according to occupation.Results Farmers were mainly concerned about the quality of vaccines (adjusted OR (aOR): 3.18, 95% CI (CI): 1.83 to 5.54). Among civil servants, media publicity reduced hesitancy (aOR: 0.44, 95% CI: 0.21 to 0.92). Among medical staff, concerns about a short duration of protective effects increased hesitancy (aOR: 8.31, 95% CI: 2.03 to 33.99). For most occupations, concerns about side effects, poor protective effects and health status increased hesitancy. In contrast, protecting oneself and protecting others acted as a stimulus to decrease hesitancy. Interestingly, ‘people around me have been vaccinated’ was associated with higher vaccination hesitancy among farmers (aOR: 2.19, 95% CI: 1.20 to 4.00).Conclusion The association of vaccination concerns and stimuli with vaccination hesitancy varied by occupation. The characteristics and concerns of specific target audiences should be considered when designing informational campaigns to promote vaccination against COVID-19.